Sensible tax policies in open economies - Hines, James R. (Statistical and Social Inquiry Society of Ireland, 2004)
This paper evaluates the design and the desirability of business taxes in small open economies, in light of evidence of the impact of taxation on the activities of multinational firms. The high degree of international capital mobility implies that small countries benefit by reducing their tax rates below the rates of other countries with whom they compete, possibly to the point of eliminating any taxes on inbound investment. Countries likewise have incentives not to tax the foreign incomes of resident companies. Host countries that are tempted to use their tax systems to subsidize and thereby encourage local employment, net exports, research, or other activities of foreign investors may do so effectively, but greater targeted activity of this kind typically comes at significant cost to the local economy. Particular attention is paid to the experience of low rates of Irish taxation.
Read before the Society, 23 October 2003
Keywords: Foreign direct investment; Foreign tax credit; Corporate taxation; 314.15